Influence of abiotic variables on phytoplanktonic morphofunctional groups of a tropical eutrophic reservoir in the state of Pernambuco (Research, Society and Development, 2022)
Phytoplankton comprises the food base in the aquatic environment, being formed by photosynthetic autotrophic organisms. Its growth in the ecosystem depends on the influence of abiotic climatic and physical-chemical variables of the water, which act in synergism in the environments. The phytoplankton community is represented by organisms that have different morphofunctional characteristics that allow their adaptation in different aquatic ecosystems. This study aimed to evaluate the influence of climatic and physicochemical variables of water on the density of phytoplanktonic morphofunctional groups in a eutrophic reservoir located in the metropolitan region of Recife (Pernambuco, Brazil). The collections were carried out in 2 different points of the reservoir, including both dry and rainy periods. The samples were stored in amber glass vials and preserved in a 4% formaldehyde solution and refrigerated at 4°C. The physical-chemical analyzes of the water followed a specific methodology. Quantitative analysis of the phytoplankton community was performed by counting in Sedgewick-Rafter chambers with the aid of an inverted microscope, with a 400x magnification, using specific dichotomous keys. To assess the influence of abiotic variables on phytoplanktonic morphofunctional groups, the free software R, version 2.1.1 was used. In the period of analysis, a greater abundance of the functional group S1 was identified, being constituted by cyanobacteria with the characteristic of being better adapted to environments with shading. It was observed that the relative humidity of the air and the apparent color of the water had a significant influence on the phytoplanktonic morphofunctional groups.